OVERVIEW GINGIVAL HYPERGROWTHS CORRELATED WITH ETIOLOGICAL FACTORS - Carolina Susanu; Sergiu Focșăneanu; Mariana Ilie; Ionuța Grigore; Alina Mihaela Călin; Anca Irina Grădinariu; Kamel Earar (Romanian Society of Oral Rehabilitation, 2022)
Gingival hypergrowth is a form of gingivitis that belongs to periodontal diseases Clinical observations coupled with the specificity of the tissue where the hormone is located, identification of hormone receptors as well as hormone metabolism have suggested that periodontal tissues are target tissues for androgens, estrogens and progestins. The etiologies of periodontal endocrinopathies are very diverse, but it is no less true that periodontal pathologies can be the consequence of the actions and interactions of sex steroid hormones with specific cells in the periodontium .The homeostasis of multicellular organisms is the result of the intercommunication between the endocrine, nervous and immune systems.